Pemodelan Prioritas Pemanfaatan Potensi Air Situ Berbasis Konservasi Sumberdaya Air - Hadihardaja, Iwan K. (Department of Civil Engineering, Diponegoro University, 2004)
Degradation function of Situ Gede (Lake Gede) becomes crucial at present time compared to its function at initial condition when it was used forÂ tourism, irrigation, and raw water supply within an optimal use. The crucial aspects are related to the decreasing reliability of supply to Situ Gede and increasing sedimentation accumulation. The research concerns with various aspects due to the Situ Gede conservation and restoration that is aimed to increase the potential uses, based on the quantitative and qualitative model by using optimization technique and Analitic Hierarchy Process (AHP). The optimization technique is applied in order to evaluate the amount of monthlyÂ water availability within 3 scenarios i.e. tourism ounly (Scenario 1), tourism and irrigation (Scenario 2), and, tourism, irrigation and raw water (Scenario 3), respectively, based on the potency of Situ Gede itself, new additional supply from other sources, and additional supply from Galunggung Crater. In addition, based on simulation of accumulated sedimentation model, that is aimed to identify the effect of firm outflow change of Situ Gede Release, indicates the decrease of firm outflow around 0,5% annually. The priority order based on AHP evaluation shows that the the first priority is Scenario 1, the second is Scenario 3 and the third is Scenario 2. Those priorities based on various criterias such as Investment Cost and Operation Maintenance, Additional Supply Reliability to Situ Gede, and Sedimentation. Sensitiviy analysis is also applied based on the weight change of each criteria in performing the shift possibilities due to the priority order. Key Words : Non Linear Programming Modeling,Â Simulation, Multi objective-Multi Criteria